Climate change, gender, and nutrition linkages: Research priorities in Cambodia - Ringler, Claudia; Thomas, Timothy S.; Choufani, Jowel; Theis, Sophie; Bryan, Elizabeth; Bhandary, Prapti; Visocky, Mark; Harvey, Jeannie; Soule, Meredith (International Food Policy Research Institute, 2017)
Agriculture is extremely important to Cambodia, representing at least one-third of the nation’s gross domestic product and providing employment to around 60 percent of the labor force. It is perhaps the most sensitive sector to changes in climate, with higher temperatures stressing plants, livestock, and workers, and rainfall variation through droughts and floods leading to crop losses and food insecurity. While it is important to consider the impact of climate change on agricultural production, it is also important to consider other cross-cutting issues to achieve the goals of Feed the Future and the Global Food Security Strategy—especially gender and nutrition. This policy note summarizes assessments of these linkages in Cambodia under the Gender, Climate Change, and Nutrition Integration Initiative (GCAN).